2016
DOI: 10.1111/ggi.12674
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between sarcopenia and household status and locomotive syndrome in a community‐dwelling elderly women in Japan

Abstract: Age, body mass index, dietary variety score, locomotive syndrome and household status were associated with sarcopenia. Early interventions are required for older adults identified as having a higher risk of sarcopenia to prevent its adverse health consequences. Geriatr Gerontol Int 2017; 17: 54-60.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 25 publications
(50 reference statements)
2
23
1
Order By: Relevance
“…In the present study, the prevalence rate of sarcopenia was 31.2% in women, whereas it was 21.0% in Japanese community‐dwelling older women in another study . In patients with RA, loss of muscle mass and strength are accelerated compared with those in the healthy population .…”
Section: Discussioncontrasting
confidence: 55%
“…In the present study, the prevalence rate of sarcopenia was 31.2% in women, whereas it was 21.0% in Japanese community‐dwelling older women in another study . In patients with RA, loss of muscle mass and strength are accelerated compared with those in the healthy population .…”
Section: Discussioncontrasting
confidence: 55%
“…Dear Editor, In a recent study published in this journal, Momoki et al reported that age, body mass index (BMI), dietary variety score (DVS), locomotive syndrome and household status were associated with sarcopenia. 1 This study showed the early intervention point for older women to prevent sarcopenia. Prevention is particularly important, because sarcopenia is associated with impairment and functional decline.…”
Section: Relationship Between Sarcopenia and Household Status In Commmentioning
confidence: 78%
“…In a recent study published in Geriatrics & Gerontology International, Nakagawa et al reported important findings. 1 Regular gum chewing exercises (GCE) might improve resting saliva secretion and occlusal force, and contribute to the prevention of malnutrition and maintenance of quality of life in frail older people. However, we have several concerns regarding the methodological procedures of the research.…”
Section: Correlation Between Nutritional Status and Frailty Regardingmentioning
confidence: 99%
“…This concept is considered important in Japan's aging society. Several studies have indicated that physical performance 7,8) , osteoporosis 9) , sagittal spine imbalance, and sarcopenia 10) are indicators for LS. "Sarcopenia," defined as a reduction of muscle mass, muscle strength, and physical performance, was associated with functional decline over a 2-year period in elderly Japanese 11) .…”
Section: Introductionmentioning
confidence: 99%